Land use land cover change in mountainous watersheds of middle Himalayas, Nepal - Gautam, Basanta Raj; Joshi, Paban Kumar (Journal on Geoinformatics, Nepal, 2009)
The study was aimed at examining land use dynamics in two typical mountain watersheds in Rasuwa district in the central development region of Nepal, namely Chileme and Bamdang. A comparative change analysis was performed for the last three decades i.e. 1976–1988, 1988–2000 and 2000–2006 using RS & GIS technology. The analysis was based on the multitemporal Landsat and IRS images taken in December 1976, December 1988, December 2000 and January 2006. During the last three decades, forest cover has been reduced drastically with increasing population pressure and agricultural expansion. Some limiting factors such as socio-economic setup and policies have also contributed to these changes and resultant land use in the watersheds.